IMPLEMENTASI EDUPRENEURSHIP DI SMAN 5 KOTA GORONTALO DALAM MATA PELAJARAN PRAKARYA - Qiran Qiran; Moh. Marham Mubaraq Lumi; Ali Alhasni; Imam Mashudi (LPPM Universitas Muhammadiyah Gorontalo, 2025)
This study aims to describe the implementation of entrepreneurship learning through the Craft and Entrepreneurship subject at SMAN 5 Gorontalo City, as well as to identify the challenges, efforts, and strategies undertaken by the school in fostering students’ entrepreneurial spirit. The research employed a descriptive qualitative approach using interview techniques with an experienced teacher who is directly involved in the entrepreneurship learning process. The findings reveal that entrepreneurship learning is not limited to theoretical understanding but is integrated with practical activities such as business plan projects, environmental observation, and digital marketing simulations. Teachers play an active role in guiding students to develop business ideas based on local potential and to utilize digital technology as part of modern learning practices. However, several challenges were identified, including limited teachers’ practical entrepreneurship competencies, low student motivation, inadequate facilities and business capital, and limited collaboration with external business partners. To address these challenges, the school has implemented various strategies, such as providing entrepreneurship training for teachers, applying project-based learning models, organizing student bazaars or entrepreneurship expos, and establishing partnerships with local micro, small, and medium enterprises (MSMEs). The school also encourages the use of portfolio- and project-based assessments to allow students to present their work more authentically. Overall, entrepreneurship learning at SMAN 5 Gorontalo City demonstrates a positive direction toward contextual and experiential learning. Strengthening collaboration among teachers, industry partners, parents, and local government is recommended to optimize the implementation of edupreneurship education and to develop creative, innovative, and economically independent students